A qualitative exploration into young children's perspectives and understandings of emotional difficulties in other children. (January 2013) - Dixon, Clare; Murray, Craig; Daiches, Anna
Research into children's perspectives and understandings of emotional difficulties is limited and methodologically varied. In this paper we explore young children's perspectives and understandings of emotional difficulties in their peers. We conducted five focus groups involving a total of 25 children. The children, aged eight and nine, were presented with vignettes representing peers experiencing emotional difficulties, and invited to discuss their perspectives on possible causes. We also explored their emotional and behavioural reactions to the vignette characters. Using interpretative phenomenological analysis we identified three themes: Searching for an Explanation; Empathy versus Blame; and Consequences and Solutions. The children drew on their own emotional experiences in their sense-making, and the extent to which they held the character responsible for their behaviour was particularly important in influencing their responses towards the characters.